Burden and determinants of scabies in Ethiopian school age children: A systematic review and meta-analysis with public health implications. - Lidetu Demoze; Fetlework Gubena; Eyob Akalewold; Helen Brhan; Kassaw Chekole Adane; Tigist Kifle; Natnael Gizachew; Zemichael Gizaw; Amensisa Hailu Tesfaye; Gelila Yitageasu (PLoS ONE)
Background Scabies is a major global health problem, affecting an estimated 200 million people worldwide and causing more than 455 million new cases annually. It is one of the most prevalent dermatological conditions in developing countries and vulnerable populations, such as school-age children. In Ethiopia, findings regarding the prevalence and associated factors of scabies among school age children have been irregular and inconsistent. In addition, no previous systematic reviews or meta-analyses have been conducted in Ethiopia. Therefore, this systematic review and meta-analysis was conducted to estimate the pooled prevalence of scabies and their associated factors among school age children in Ethiopia. Methods We conducted a systematic literature search (April 9-12, 2024) to identify studies on scabies incidence and associated factors in Ethiopian children among school age children. Published and peer reviewed articles were searched in electronic databases such as Medline/PubMed, Embase, Scopus, Science Direct, and Epistemonikos. In addition, other search methods, such as Google Scholar, Ethiopian University and Research Institutional Repository, and Google manual searches were also conducted. All papers published until 12 April 2024 were considered. We conducted a systematic review and meta-analysis using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Only studies that met the predefined inclusion criteria were included. Quantitative methods were employed to analyze the data, and heterogeneity across studies was assessed. Additionally, publication bias was evaluated via a funnel plot and Egger's regression test. Publication bias was assessed via funnel plots and Egger's regression test. The protocol for this review has been registered with PROSPERO (ID: CRD42024532037). Results A comprehensive systematic review of 1,144 studies identified 16 studies that met the inclusion criteria were included in this systematic review and meta-analysis. The pooled prevalence of scabies among school age children in Ethiopia, based on the 16 included studies, was 21.1% (95% CI: 15.0%, 27.2%). A family history of scabies, knowledge about scabies, sharing a bed, sleeping with a scabies-ill person, sharing a cloth, contact with a person who has symptoms of scabies, and sleeping place are some of the factors significantly associated with scabies among school age children in Ethiopia. Conclusions The pooled prevalence of scabies among school age children in Ethiopia was high. Sociodemographic, water, sanitation, and hygiene factors were associated with scabies. A multi-pronged approach is recommended to address scabies in Ethiopian school age children. Strengthening collaboration among the education, water, and health sectors would promote a coordinated response. Such interventions have the potential to reduce the prevalence of scabies in this vulnerable population significantly.